PROFIL KETERAMPILAN ARGUMENTASI ILMIAH PESERTA DIDIK PADA MATERI OPTIK DAN FLUIDA (Universitas PGRI Sumatera Barat, 2022)
Scientific argumentation ability is one of the important things to support students in learning to think critically, act, and communicate supported by data or evidence. Scientific argumentation skills include 4C skills, namely communication. Among the indicators of scientific argumentation are claims, data, warrants, backing, rebuttal and qualifiers. The purpose of this study was to determine the scientific argumentation skills profile of students at MAS Manba'ul Huda Bandung. The research method used is descriptive with a qualitative approach. The subjects of this study were 22 people from class X1 (11) MIPA. To find out the level of scientific argumentation skills, students are given 2 physics questions related to argumentation-based optics and fluids. The results found that students' scientific argumentation skills were still relatively low. This is shown from the level of students' scientific argumentation skills, most of which are in the good to weak category, namely 27% very weak, 14% weak, 18% sufficient, and 34% good.Keywords : Teaching Materials, Physics, Argumentation Skills